A latent green fluorescent styrylcoumarin probe for the selective growth and detection of Gram negative bacteria. Issue 16 (1st September 2018) - Váradi, Linda; Wang, Miaoyi; Mamidi, Ramesh R.; Luo, Jia Lin; Perry, John D.; Hibbs, David E.; Groundwater, Paul W.
Graphical abstract: Abstract: A novel, green fluorescent β-alanylstyrylcoumarin derivative was synthesized and evaluated for its performance as a fluorogenic enzyme substrate on a range of clinically relevant microorganisms. The substrate was selectively hydrolysed by β-alanyl aminopeptidase producing P. aeruginosa resulting in an on-to-off fluorescent signal. Growth inhibitory effect of the substrate was observed on Gram positive bacteria and yeasts. Meanwhile, Gram negative species, despite their extremely protective cell envelope, showed ready uptake and accumulation of the substrate within their healthy growing colonies displaying intense green fluorescence.